A histopathological study of smoking on free gingiva in patients with moderate to severe periodontitis - Maryam Seyedmajidi; Parand Keshavarzi; Ali Bijani; Reza Faraji; Neda Babaee (Babol University of Medical Sciences, 2013)
Introduction Cigarette smoking has been recognized to be a risk factor for progression of periodontal disease. Due to less inflammation and bleeding in the presence of clinical signs of periodontal disease in smokers than in nonsmokers and given the conflicting results of studies on changes in the epithelium and gingival connective tissue by smoking, this study was performed to evaluate the thickness and keratosis on the epithelium of free and sulcular gingival tissue in smokers and nonsmokers patients with moderate to advanced periodontitis. Methods: In this cross sectional study, biopsies were obtained from palatal gingival of 60 patients with moderate to advanced periodontitis (30 smokers and 30 nonsmokers). These biopsies were histologically processed, serially sectioned at 5 microns, stained with H. E. and examined by image analysis software (analysis-SL-starter), which was used to perform the morphometric evaluation of the outer and inner epithelial thickness, keratosis and vascularity in connective tissue. The data were analyzed with SPSS 17, t-test, Mann-Whitney Test, and Pearson correlation. p<0.05 was considered significant. Results: Histopathological examination showed significant association between smoking and CAL (p=0.048), keratosis on outer epithelium (p=0.020) and mean of thickness of outer (p=0.023) and inner (p<0.001) marginal gingival epithelium but gingival vascular density in nonsmokers was more than smokers (p=0.002). Collagenized connective tissue was observed in smokers more than nonsmokers. (p>0.001) Conclusions: It seems that the reduction of the clinical signs of inflammation in the gingival tissue of smokers is due to changes in gingival epithelium and connective tissue from smoking.